2003
DOI: 10.1136/thorax.58.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Health effects associated with smokeless tobacco: a systematic review

Abstract: Background: It is believed that health risks associated with smokeless tobacco (ST) use are lower than those with cigarette smoking. A systematic review was therefore carried out to summarise these risks. Methods: Several electronic databases were searched, supplemented by screening reference lists, smoking related websites, and contacting experts. Analytical observational studies of ST use (cohorts, case-control, cross sectional studies) with a sample size of >500 were included if they reported on one or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
219
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(223 citation statements)
references
References 84 publications
0
219
2
2
Order By: Relevance
“…4 Use of oral tobacco (chewing tobacco and tobacco mixtures such as paan) has also been linked to oral cancers. 5 Little is known about awareness of mouth cancer in the UK population. The most recent study involved focus groups in northern England and reported low levels of awareness in a group of older male drinkers and smokers.…”
Section: Introductionmentioning
confidence: 99%
“…4 Use of oral tobacco (chewing tobacco and tobacco mixtures such as paan) has also been linked to oral cancers. 5 Little is known about awareness of mouth cancer in the UK population. The most recent study involved focus groups in northern England and reported low levels of awareness in a group of older male drinkers and smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Both smoked and smokeless, forms of tobacco are associated with increased risk of chronic and terminal diseases (Critchley et al, 2003;Gupta et al, 2003;Nair et al, 2004;Krishna et al, 2013). These diseases include destructive periodontitis (Cutress, 2003;Gupta et al, 2003;; oral and oropharyngeal cancers (Johnson et al, 2011;Radoi et al;2013); oral potentially malignant disorders, notably leukoplakia, erythroplakia, and oral submucous fibrosis (Warnakulasuriya et al, 2007) and cardiovascular disorders including stroke .…”
Section: Introductionmentioning
confidence: 99%
“…Different product types have differing disease profiles, depending on ingredients and manufacturing techniques, but all SLT products are potentially addictive, some delivering even higher doses of nicotine than cigarettes. In addition, chewing tobacco and snuff contain 28 carcinogens which are significantly associated with various types of cancers mainly including of oral cavity, upper gastro-intestinal track and of the head and neck (Critchley & Unal, 2003;Khawaja, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%